ANALISIS KETERLAKSANAAN PRAKTIKUM BIOLOGI DI SMA NEGERI 9 MAKASSAR - Rahman, Muhammad Afuw; B, Nurhayati; Andi Rahmat Saleh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the implementation of Biology laboratory activities at SMA Negeri 9 Makassar based on three stages: preparation, implementation, and closing activities. This research employed a descriptive quantitative approach involving 137 eleventh-grade Biology students as respondents. Data were collected through a Likert-scale questionnaire consisting of 30 statements and were supported by interviews and observations of Biology teachers. The data were analyzed descriptively by calculating the mean scores for each indicator of laboratory implementation. The results indicated that the overall implementation of Biology laboratory activities was categorized as good, with a mean score of 4.04. The preparation stage obtained a mean score of 4.02, the implementation stage 4.17, and the closing stage 3.96, all of which were classified as good. The implementation stage achieved the highest score, while the closing stage showed a relatively lower score although it remained in the good category. These findings were supported by interview results indicating that teachers had conducted laboratory activities systematically; however, several constraints remained, particularly limited laboratory equipment and instructional time. Therefore, improvements are needed in evaluation and laboratory report preparation as well as in providing adequate laboratory facilities to optimize the implementation of Biology laboratory activities.